Effects of priming on Muslims' behavior: an empirical study - Badi, Jamal Ahmed Bashier; Ayinde, Olorogun Lukman (Centre for Promoting Ideas, USA, 2013)
Studies on the effects of priming religious people are not a new phenomenon for Christians and Jews. However, it appears there is no such study on the effects of priming on Muslims. As such, this research is an empirical study that test and shows the reactions of the Muslim respondents to priming. Data was collected and regression analysis was, used arrive at the results. The results show that immediately the respondents were primed with a certain sect's or a creed they try to demonstrate specifics characteristics according to the sect's ideology. This appears in both actions and ideology during responds to the questionnaire.